Nina Dzhydzhora. The use and stylistics of sociolects and territorial dialects in Nisha Kanako's novel “Sakura” - Dzhydzhora, Nina (Young Scholars Grinchenko – Seton International Journal, 2022)
The research discusses the use of regional dialects and sociolects through the works of modern female Japanese authors, their stylistics, and their function within the speech portrait of characters. The relevance of the research is based on the role of Japan in the modern world and the importance of regional dialects and sociolects for interpersonal communication with the Japanese. The aim of the research is to analyze elements of regional dialects and sociolects within the context of literature and determine their stylistics and uniqueness and solidify the importance of further analysis of regional dialects and sociolects in literary works, specifically in the novel “Sakura” by Nishi Kanako. The author analyzes elements of regional and social dialects in the dialogue between the characters, applying methods of comparative linguistics, gives context to the meaning of these elements within the novel itself, through literary analysis, and provides a clear overview of the uniqueness and style of the dialect used. The results of the research determined the stylistic features and usage of regional dialects and sociolects in the chosen literary work, their function within those works, and society as a general, as depicted in modern literature based on the speech portraits of characters. The conclusion fixed the importance of researching regional dialects and sociolects through the medium of literary works and laid the groundwork for future research.